The Impact of Resilience Interventions on University Students' Mental Health and Well-Being: A Systematic Review - Ghalib G. Abulfaraj; Rebecca Upsher; Helena M. S. Zavos; Eleanor J. Dommett (MDPI AG, 2024)
Attending university is a time of considerable change, and there are rising concerns about the mental health and well-being of university students, leading to calls for a whole-university approach to student support. Resilience interventions offer an opportunity to improve mental health and well-being, whilst also developing a much sought-after graduate attribute. We conducted a systematic review of interventions designed to increase university students' levels of resilience and examined the impact of these on students' mental health and well-being. Five databases identified 1377 unique records, 47 of which were eligible for inclusion. Eligible studies were drawn from a range of countries and adopted different designs, with the most common being the randomised controlled trial (RCT). Interventions were classified into mindfulness, skills-based, psychoeducation, and coaching, with delivery both online and face-to-face. The most common outcomes were depression, anxiety, stress, and well-being. The 'Quality Assessment Tool for Before-After (Pre-/Post) Studies' was used to assess the risk of bias with most studies rated as fair. Overall, the studies indicated that there is little evidence of a positive effect on depression, but stress and anxiety may be reduced following interventions. Well-being data were inconclusive. Interestingly, most interventions did not impact measures of resilience or mindfulness, despite the training targeting these constructs. The available research is currently limited and there is a need for more high-quality designs providing descriptions of interventions.